Do Dynamic speed feedback signs impact drivers differently based on speeding tendencies? Insights from applications at select critical roadway contexts - Mahmud, Md Shakir; Gates, Timothy J.; Megat Johari, Megat Usamah; Jashami, Hisham; Bamney, Anshu; Savolainen, Peter T. (Elsevier, 2023)
The effects of a traffic control devices on drivers at different speed percentiles, particularly on the faster drivers, are of specific interest due to their higher likelihood of crash involvement. A study was designed to evaluate how the dynamic speed feedback signs (DSFS) affect drivers while transitioning from a high-speed to a low-speed environment. A total of 5 sites were selected, which included a freeway exit ramp, two speed transition zones, and two high-speed rural highway curves. Vehicle speed profiles approaching and entering these critical locations were collected before and after installing the DSFS. Based on the tracked speed of the free-flowing vehicles before the influence area, drivers were categorized as slower drivers, average drivers, and faster drivers using the 15th and 85th percentile speed at each site. Overall, installing the DSFS resulted in a significant reduction in speed across all locations for all sites. Drivers were found to reduce their speed while approaching the curve, traversing through the speed transition zones, and entering the curves or reduced speed limit areas. Results showed that faster drivers tend to reduce speed more than the average or slower drivers at every location. The faster drivers also reacted to the sign earlier compared to the slower or average drivers. The overall results are encouraging as they indicate that DSFS impact faster drivers more, which can ultimately reduce speeding-related crashes when transitioning from a high-speed environment. Based on the findings, the continued use of DSFS as a speed reduction strategy is recommended.